Real time monitoring and compensation system for micro electro discharge machining - Aligiri, Erwin (2011)
The rapid growth in demand for micro parts has urged today’s manufacturing industry to establish a reliable technique for micromachining. Micro Electrical Discharge Machining (EDM), the downscaled technique of conventional EDM, provides the capability of machining high strength and electrically conductive materials by means of electrical sparks. The fact that EDM is now the fourth most popular machining process, with sales exceeding all other processes except milling turning and grinding, shows that it has unique characteristics to become one of the most useful industrial techniques for machining complex three dimensional features.